The Link Between Economic Growth and Poverty in Indonesia : Hubungan Antara Pertumbuhan Ekonomi dengan Kemiskinan di Indonesia - Graciela Br Sembiring (Outline Publisher, 2023)
This paper aims to analyze the relationship between economic growth and poverty in Indonesia through a literature review using articles from the Science and Technology Index (SINTA). This analysis is based on recent findings over the past decade regarding economic growth and poverty in Indonesia. The results of the study reveal that economic growth contributes to reducing the poverty rate in the country. However, for optimal results, economic growth must be inclusive of all segments of society. The role of government is very important in ensuring fairness, honesty and accountability in policies. As a result, there has been an increase in the competence of human resources which has led to an expansion of employment opportunities and has had a positive impact on poverty alleviation in Indonesia.